Stakeholder Engagement and Responsible Research & Innovation in promoting Sustainable Development and Empowerment through ICT - Wakunuma, Kutoma; Jiya, Tilimbe (European Journal of Sustainable Development, 2019)
ICT plays a significant role in both developed and developing countries across the globe. ICTs are also seen as playing an important role in achieving the UN’s Sustainable Development Goals (SDGs). In particular, their importance is seen in terms of achieving sustainable development in the areas of health, education, social inclusion, global partnership and empowerment, among others. However, much ground cannot be made without creating and involving communities and networks that will support the sustainable use and development of ICT in emerging and developing countries. One concept that advocates for the inclusion of communities and establishment of networks around the use and development of ICT is Responsible Research and Innovation (RRI). At the core of RRI is the engagement of different stakeholders within communities and networks that are involved with ICT development in emerging and developing countries to ensure sustainable development. Using stakeholder theory, we introduce the work being conducted in the Responsible Research and Innovation Networked Globally (RRING) project to highlight the important role of stakeholders as part of RRI in the use and development of ICTs in emerging and developing countries. In particular, we will discuss how stakeholder engagement as part of RRI can be understood in an emerging country like India, specifically through our discussion of a women’s artisan handicraft centre known as Gramshree in the heart of Ahmedabad, India. We aim to highlight aspects of stakeholder engagement, the role of stakeholders in implementing ICTs in women’s sustainable development and empowerment. The aim is to showcase how sustainable development and empowerment could be achieved through the formation of a community network around ICT use and development. Keywords: Sustainable Development, Responsible Research and Innovation, ICT, Women Empowerment, Stakeholder Engagement